Strategic Planning in the Construction Companies in Oman - Al-Ghrairee, Layth; Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2020)
This research aims to evaluate the role of strategic planning in construction companies in Oman and to know to which level the strategic planning is used in this sector as well as the efficiency of that use in the different sizes of companies. There will be an evaluation of the components of strategic planning as well as the success factors in strategic planning with a brief focus on the challenges of strategic planning. One very important factor for each organization to stay strong is to have a successful strategic planning. The successful strategic planning needs some key factors to achieve true success. These factors will be investigated in this research.